Classifications of ξ(s)-QSO on 2D simplex - Mukhamedov, Farrukh; Saburov, Mansoor; Qaralleh, Izzat (2012)
In the paper, it was given classification of ξ(s)-quadratic stochastic operators in the 2D simplex. Apart from this, it were studied asymptotic behaviors of operators from some classes